Clinical characteristics, viral dynamics, and antibody response of monkeypox virus infections among men with and without HIV infection in Guangzhou, China - Yang, Huiqin; Xie, Xiaoqing; Zeng, Mou; Cao, Yinghui; Fan, Qinghong; Jiang, Mengling; Lei, Chunliang; Wang, Jian; Li, Feng; Tang, Xiaoping; Yu, Haisheng; Li, Linghua (Frontiers in Cellular and Infection Microbiology, 2024)
Background: Monkeypox virus (MPXV) is spreading globally and nearly half of the infected people were human immunodeficiency virus (HIV) positive. Therefore, an in-depth understanding of the effects of HIV infection on the outcomes of MPXV infection is urgently needed. This study aimed to explore the clinical features, viral dynamics, and antibody response to MPXV infections in men who had sex with men (MSM) with and without HIV co-infection. Design or methods: MPXV-infected patients diagnosed by PCR were recruited in this study and were divided into MPXV and MPXV + HIV groups based on whether they were co-infected with HIV. Clinical data and samples were collected during of the hospital stay and follow up interviews. The symptoms and signs, laboratory examinations, viral shedding in various body fluids or swabs, antibody dynamics were tracked and compared between the two groups. Results: A total of 41 MPXV patients were recruited through June 2023 to September 2023 in Guangzhou. The MPXV group and MPXV + HIV group comprised 20 and 21 MSM, respectively. Patients in the two groups exhibited similar clinical characteristics except for pruritus and eschar, both were significantly fewer in MPXV + HIV group than in MPXV only group. Among the 355 clinical samples collected, MPXV DNA was detected in 100% of scabs, 97.4% of skin swabs, and 92.3% of exudate swabs from lesions, while the positive rate was 87.5% from oropharyngeal swabs, 59% from saliva, 51.3% from anal swabs, 50% from feces, 30.6% from urine samples, 37.5% of semen, and 28.2% from sera. Dynamics analysis revealed that viral DNA was undetectable in most patients 20 days after symptom onset. IgM and IgG antibodies to MPXV were detected in all patients with 3-5 days earlier in the MPXV group than in the MPXV + HIV group. Conclusion: This cohort analysis based on a large outbreak among MSM in Guangzhou indicated no obvious differences in clinical symptoms, viral DNA data, but antibody responses were 3-5 days later in mpox patients with HIV infection.